Anticipating organized and transnational crime - Williams, Phil (Crime, law and social change, 2002)
This paper seeks to identify ways in which governments and lawenforcement agencies might enhance the effectiveness of their efforts to anticipate organized crime. It starts by defining what is meant by anticipation, and differentiating it from the much more difficult task of prediction. The analysis then identifies some of the methods and models that are generally accepted as part of the existing knowledge base on organized crime and highlights how these can be used to anticipate future developments and to develop warnings about how criminal organizations might evolve and behave in the future. The knowledge base includes political, economic, sociological, strategic, and composite models and shows how they provide a foundation for anticipating future developments inorganized crime. The models are either models about the kind of environment in which organized crime flourishes or models about the ways in which organized crime behaves. What we do, in effect, is to identify and elucidate "models" in ways that provide propositions about the kinds of developments, innovations or changes we might see in organized crime (both domestic and transnational) in the future. Underlying indicators provide warning about future manifestations of organized crime. Anticipating these manifestations provides a basis for appropriate preventive, defensive or mitigating strategies. Finally, the article provides some examples of specific techniques of information collection and intelligence analysis that might assist in this task of anticipation.